1998
DOI: 10.1111/1468-2435.00051
|View full text |Cite
|
Sign up to set email alerts
|

Migrant Remittances in Greece and Portugal: Distribution by Country of Provenance and the Role of the Banking Presence

Abstract: The article examines migrant remittances per country of origin of remittances for two emigration countries, Greece and Portugal. It also examines the relationship between remittances and the number of banks of the emigration country in the host country.From the analysis it appears that remittances are concentrated in a small number of host countries -the US and Germany for the Greek case; France (mainly) and the US, Germany and Switzerland for the Portuguese case.Remittances followed similar trends, characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…Hence, we could argue that financial gains from migration (in the form of remittances) are extremely low in the case of Greece , thus augmenting the negative impacts of brain drain for the country. This finding is very important, as Greek emigrants' remittances have held a crucial role for the national economy, especially after 1980 (Karafolas, ). Lianos (), for example, argues that migrant remittances from Germany only accounted for more than 1% of gross national product in 1982, and this type of currency flow represented, together with tourism, the main source of currency earnings for the country during the period 1980–2000.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we could argue that financial gains from migration (in the form of remittances) are extremely low in the case of Greece , thus augmenting the negative impacts of brain drain for the country. This finding is very important, as Greek emigrants' remittances have held a crucial role for the national economy, especially after 1980 (Karafolas, ). Lianos (), for example, argues that migrant remittances from Germany only accounted for more than 1% of gross national product in 1982, and this type of currency flow represented, together with tourism, the main source of currency earnings for the country during the period 1980–2000.…”
Section: Resultsmentioning
confidence: 99%
“…As regards the macroeconomic determinants of worker remittances, the black market foreign exchange premium and the presence of domestic banks in the host country have been identified to strongly affect the size of officially registered remittances (El‐Sakka and McNabb, 1999; Karafolas, 1998; Russell, 1992). Remittances are also responsive to changes in the interest rate differential between the home and the host country, government policies, the level of economic activity both in the host and in the home country, wages, political risk, and the rate of inflation.…”
Section: The Economics Of Workers Remittances: Earlier Evidencementioning
confidence: 99%
“…Karafolas and Sariannidis (2009) found that the development of the banking network of Greek and Italian banks in Albania favoured the growth of remittances of Albanian immigrants through the banking system. Karafolas (1995Karafolas ( , 1998 found that banks from Greece, Italy, Portugal and Spain created a banking network in countries where an immigrant population from those countries reside. Amuedo-Doranes and Pozo (2005) working on the case of Mexican immigrants, conclude that educated immigrants and those who have a network of friends and family in the host city, use the banking system to transfer their savings to Mexico.…”
Section: Introductionmentioning
confidence: 99%